2017
DOI: 10.1080/07388551.2017.1331337
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of potato peel: a biorefinery approach

Abstract: Potato is the fourth main crop consumed worldwide and is an important constituent in the human diet. Consequently, potato is widely used in food-processing industries. However, these industries generate massive amounts of potato peel (PP) as a by-product, which is usually considered a waste, and is discarded. Interestingly, recent research suggests that PP is a valuable source of bioactive compounds, which can be converted into value-added products. In this study, we review the physicochemical composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 66 publications
1
56
0
4
Order By: Relevance
“…Use of PPW for the recovery of antioxidant phenolic compounds not only provides economic benefits but also an opportunity to reduce environmental and sanitation problems (Al‐Weshahy & Rao, ; Amado et al ., ). PPW is one of the major agro‐waste that can be valorised into a number of value‐added products (Pathak et al ., ). Valorisation of PP waste can omit severe disposal‐related problems having environmental concerns such as microbial spoilage, as it is a good source of dietary fibre and antioxidants (Amado et al ., ).…”
Section: Valorisation Of Potato Peelmentioning
confidence: 97%
See 2 more Smart Citations
“…Use of PPW for the recovery of antioxidant phenolic compounds not only provides economic benefits but also an opportunity to reduce environmental and sanitation problems (Al‐Weshahy & Rao, ; Amado et al ., ). PPW is one of the major agro‐waste that can be valorised into a number of value‐added products (Pathak et al ., ). Valorisation of PP waste can omit severe disposal‐related problems having environmental concerns such as microbial spoilage, as it is a good source of dietary fibre and antioxidants (Amado et al ., ).…”
Section: Valorisation Of Potato Peelmentioning
confidence: 97%
“…Moreover, PPE can be used as a dietary antioxidant ingredient in food to reduce oxidative stress and prevent the progress of chronic and degenerative diseases (Singh & Rajini, , ; Singh et al ., ). Studies have reported the potential of PP as a valuable ingredient in food formulations to improve nutritional quality and to retard oxidation (Al‐Weshahy & Rao, ; Pathak et al ., ).…”
Section: Health‐promoting Activities Of Potato Peelmentioning
confidence: 97%
See 1 more Smart Citation
“…The massive waste generation during industrial processing of potato tubers has drawn attention, and some alternatives have been developed for its sustainable use. In this sense, strategies for the valorisation of those residues have been explored, and applications including the use of such wastes as a source of ingredients for the food and pharmaceutical industries and their utilisation for energy production, and animal feed have been explored (Galhano dos Santos et al , ; Gebrechristos & Chen, ; Pathak et al , ). Researchers have shown that potato processing wastes can be an important source of compounds such as proteins, starch, glycoalkaloids (Priedniece et al , ; Gebrechristos & Chen, ), dietary fibre (Schieber & Saldaña, ; Scharf et al , ) and phenolic compounds (Singh & Saldaña, ; Singh et al , , ; Wijngaard et al , ; Akyol et al , ; Kumari et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that potato processing wastes can be an important source of compounds such as proteins, starch, glycoalkaloids (Priedniece et al , ; Gebrechristos & Chen, ), dietary fibre (Schieber & Saldaña, ; Scharf et al , ) and phenolic compounds (Singh & Saldaña, ; Singh et al , , ; Wijngaard et al , ; Akyol et al , ; Kumari et al , ). Due to the valuable composition, biorefinery approaches using potato peel as biomass to convert it into an array of products by means of different paths and processing methods have been proposed (Ahokas et al , ; Fritsch et al , ; Pathak et al , ). To the best of our knowledge, however, those studies have been developed in several potato species different from the Group Phureja.…”
Section: Introductionmentioning
confidence: 99%